Does Share of Manufacturing and Rate of Investment Help in Boosting Exports? Evidence from India Using Cointegration Analysis - Thimmavajjala, Pavan Kumar (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : The current work empirically analyzed the existence of a long-run relationship between India’s rate of exports, its rate of investment, and its share of manufacturing. It also tried to understand the impact investment and manufacturing had on exports. The need to look at India’s exports from the point of its manufacturing capacity necessitated this empirical exercise. Methodology : The Reserve Bank of India and the World Bank’s data from 1960 to 2020 were used for the analysis. The auto-regressive distributive lag (ARDL) method of cointegration, which was introduced by Pesaran et al. (2001) was utilized to investigate the possibility of a long-term association between the variables. Additionally, the Granger causality test was employed to determine the causal direction of policy effects. Findings : The ARDL test showed that a long-run relationship existed between India’s rate of exports, rate of investment, and share of manufacturing, wherein the latter positively influenced the rate of exports. This indicates that raising the rate of investment and share of manufacturing would have a multiplier effect on exports. Practical Implications : From a policy standpoint, the study advocated raising the rate of investment and the share of manufacturing to increase India’s rate of exports. Our study is not free from limitations and allows scope for future researchers to touch upon the kind of transmission. Originality : Prior research looked at the role of exports and imports in growth and linkages between FDI and trade openness. This work attempted to understand how the level of manufacturing and rate of investment influenced India’s rate of exports.